2019
DOI: 10.25258/ijddt.v9i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenugreek (Trigonella foenum graecum) seed aqueous extract on blood glucose, lipid profile and some hormonal assay in Streptozotocin induced diabetic male albino rats.

Abstract: Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia over a prolonged period, since a long time, diabetes has been treated with plant medicines, one of these important plant is Trigonella foenum-graecum (fenugreek), thus, the investigation goals of this study to clarify the role of fenugreek seed aqueous extract in its therapeutic dose on blood glucose , triglycerides, total cholesterol, lower density lipoprotein( LDL), higher density lipoprotein (HDL),very lower density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The current study showed a resemblance with the literature study performed by Chalabi et al. (2019) and Sekhar et al. (2024), in which diabetic group exhibited a significant decline ( p < 0.05) in total cholesterol (TC) level treated with T. foenum gracum for 42 days in a dose‐dependent manner.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The current study showed a resemblance with the literature study performed by Chalabi et al. (2019) and Sekhar et al. (2024), in which diabetic group exhibited a significant decline ( p < 0.05) in total cholesterol (TC) level treated with T. foenum gracum for 42 days in a dose‐dependent manner.…”
Section: Resultssupporting
confidence: 89%
“…Cholesterol levels of groups T3-T5 were reduced at the end of the study through the supplementation of FS and BCS. The current study showed a resemblance with the literature study performed by Chalabi et al (2019) and Sekhar et al (2024), in which diabetic group exhibited a significant decline (p < 0.05) in total cholesterol (TC) level treated with T. foenum gracum for 42 days in a dose-dependent manner. However, for N. sativa seeds, study findings were consistent with the study (Al-Logmani & Zari, 2011), in which BCS significantly (p < 0.001) increased levels of HDL-cholesterol and significantly (p < 0.001) reduced LDL-cholesterol in streptozotocin-induced diabetic models.…”
Section: Notesupporting
confidence: 85%
“…Glucose levels were decreased in the PE-TFG-treated groups. These results are supported by Al-Chalabi et al, who stated that diabetic rats were treated with 300 mg/kg of methanolic fenugreek seed extract for 4 weeks, significantly decreasing blood glucose levels (Al-Chalabi et al 2019 ). 4-hydroxy isoleucine from TFG seed extract increased insulin secretion in human and rat pancreas and inhibited hepatic glucose production (Zafar and Gao 2016 ).…”
Section: Discussionsupporting
confidence: 54%